Outcome comparison of rotational ankle fractures: Supination external rotation versus pronation external rotation - Min-Su Lee; Gun-Woo Lee; Ji-Hoon Choi; Keun-Bae Lee (PLoS ONE, 2025)
Background Ankle fractures are among the most common types of fractures in the orthopaedic field, and the Lauge-Hansen classification is commonly used to categorize rotational ankle fractures. This study evaluated and compared the clinical and radiological outcomes of surgically treated supination external rotation (SER) and pronation external rotation (PER) injuries of grades III or IV. Methods We retrospectively reviewed and enrolled 104 patients who underwent open reduction and internal fixation for SER or PER injuries classified as Grades III or IV between January 2016 and December 2021, all performed at a single center. Of these, 72 belonged to the SER group and 32 to the PER group. The average postoperative follow-up durations were 31.3 months (range, 24 to 74) for the SER group and 32.1 months (range, 24 to 71) for the PER group. Clinical and radiological outcomes were assessed 24 months after surgery and compared between the two groups. Details of concomitant surgical procedures performed and postoperative complications were also evaluated. Results All clinical outcome variables, including the Foot and Ankle Outcome Score, Visual Analog Scale for pain, and ankle range of motion, were comparable between the two groups. Similarly, no statistically significant differences were observed in the development of post-traumatic arthritis or in the frequency of syndesmotic widening 24 months postoperatively. However, the time required for fibular union was significantly longer in the PER group, taking 5.6 ± 2.2 months compared to 3.4 ± 1.3 months in the SER group on average (p < 0.001). Conclusions Our study demonstrated that both types of rotational ankle fractures can achieve equivalent clinical and radiological outcomes with surgical treatment. Given the prolonged time to fibular union in the PER group, careful monitoring during postoperative follow-up is required.